Improving Of Performance Characteristics Of Induction Motor Using Inverter Topologies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
This paper presents the simulation and implementation of multilevel inverter fed induction motor drive. The output harmonic content is reduced by using multilevel inverter. In symmetrical circuit, the voltage and power increase with the increase in the number of levels of inverter. The switching angle for the pulse is selected in such way to reduce the harmonic distortion. This drive system has advantages like reduced total harmonic distortion and higher torque. The model of the multilevel inverter system is developed with PWM strategy to control the induction motor. The rate of change of voltage with respect to time i.e. dv/dt is very high at these edges, of the order of 500–5000 V/μs.The two-level inverter topology has attracted attention in low power low voltage drive applications where as Three-Level inverter topology has attracted attention in high power High performances voltage drive applications. Single-phase VSI cover low-range power applications and three-phase VSI cover the medium- to high-power applications. The Main purpose of these three level inverter topologies is to provide a three-phase voltage source, where the amplitude, phase, and frequency of the voltages should always be controllable. Although most of the applications require sinusoidal voltage waveforms.